AACRAO releases snapshot report on state of international enrollment. Issue 3 (May 2017) - Sutton, Halley
Abstract : In response to concerns from international educators that the political discourse about foreign nationals in the United States during the course of the 2016 presidential campaign could be damaging to international student recruitment, the American Association of Collegiate Registrars and Admissions Officers released a snapshot survey on institutional and applicant perceptions.